HUBUNGAN USIA DAN PENGETAHUAN TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT PADA SANTRIWATI DI ASRAMA PUTRI K.H. SAHLAN ROSJIDI - Ningsih, Dwi Retno; Rusmitasari, Heni; Imron, Ali; Larasaty, Nurina Dyah (Ensiklopedia of Journal, 2026)
Backgorund: The dormitories are learning environments inhabited by many female students, making the implementation of Clean and Healthy Living Behaviors (PHBS) very important to prevent disease and maintain daily comfort. However, in the KH. Sahlan Rosjidi Female Dormitory at Unimus, the level of PHBS implementation is still relatively low. Based on observations and questionnaires conducted with 73 female students, it was found that only 49.3% of respondents had high PHBS behavior, while the other 50.7% were still classified as low. This condition is influenced by factors such as unequal knowledge, age differences, and limited facilities and infrastructure, such as the lack of PHBS posters and adequate sports facilities in the dormitory environment. The purpose: of this study was to determine the relationship between age and knowledge on the implementation of PHBS. Method: This study used a quantitative analytical method with a cross-sectional design. The study population was 270 female students with a sample of 73 respondents selected using accidental sampling. The research instrument was a questionnaire, with data analysis using univariate tests and Chi- Square tests. The results: Showed that the majority of respondents were aged 20–21 years (53.4%), had good knowledge (90.4%), and high PHBS (76.7%). The Chi-Square test showed a significant relationship between age and PHBS (p = 0.000) and knowledge with PHBS (p = 0.026). Conclusion: These results indicate that more mature age and higher knowledge play a positive role in improving PHBS implementation among female students in the dormitory. Efforts to increase knowledge and support infrastructure are important to strengthen sustainable PHBS practices.Keywords: Age, Knowledge,  PHBS, Dormitory, Female Students